Pemanfaatan limbah organik sebagai imuno herbal blok dalam peningkatan ekonomi masyarakat Desa Biting Kecamatan Badegan Ponorogo [Utilization of organic waste as immune herbal blocks in improving the economy of the people of Biting Village, Badegan Sub-District, Ponorogo] - Kurnijasanti, Rochmah; Sudjarwo, Sri Agus; Purwitasari, Neny (Buletin Pengabdian, 2024)
This Community Service aims to improve the economy of the people of Biting Village, Badegan Sub-District, Ponorogo, through the use of organic waste, increasing the knowledge and skills of the community, through the technology transfer of producing Immune Herbal Block formulations based on organic waste to increase livestock growth. The methods used in this activity are tutorial, training, demonstration, practice and mentoring. The results of the Community Service implementation showed an increase in participants' knowledge about the use of organic waste from 25.75% to 90.25% and an increase in participants' skills regarding how to prepare Immune Herbal Blocks from 20.25% to 92.20%. Apart from increasing the knowledge and skills of Community Service participants in Biting Village, Badegan Sub-District, Ponorogo District, there has been a decrease in the average cost of additional feed, medicine, and vitamins per farmer from 1,650,000 Rupiah to 800,000 Rupiah. From the results of Community Service, it is hoped that the community's economy will improve, especially for livestock farmers in Biting Village, Badegan Sub-District, Ponorogo District.